2002
DOI: 10.1007/s11906-002-0035-0
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-related hypertension: Role of the sympathetic nervous system, insulin, and leptin

Abstract: Heightened sympathetic nervous system activity, hyperinsulinemia, insulin resistance, and hyperleptinemia contribute to obesity-related hypertension. However, the precise mechanism and sequence of events in this pathophysiologic event have not been clarified. This review concentrates on studies helping to clarify the mechanisms of blood pressure elevation associated with weight change, concentrating on the temporal changes in neuroendocrine factors that are known to control energy metabolism and blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 54 publications
1
31
0
3
Order By: Relevance
“…12,17 The differences among the various studies might possibly be due to the multiple mechanisms and heterogeneous factors involved in the regulation of BP. 11,15,18 In the present study, fasting plasma insulin levels at entry were similar between those with and without weight gain and between those with and without BP elevation. However, the absolute increases in plasma insulin with weight gain were significantly greater in the group with significant weight gain and in the group with BP elevation whose BMI significantly increased.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…12,17 The differences among the various studies might possibly be due to the multiple mechanisms and heterogeneous factors involved in the regulation of BP. 11,15,18 In the present study, fasting plasma insulin levels at entry were similar between those with and without weight gain and between those with and without BP elevation. However, the absolute increases in plasma insulin with weight gain were significantly greater in the group with significant weight gain and in the group with BP elevation whose BMI significantly increased.…”
Section: Discussionsupporting
confidence: 61%
“…18,19 However, the relation of insulin resistance and sympathetic nervous overactivity to hypertension and obesity is still controversial. 11,15,20 These and other investigations have documented the coexistence of elevated UA level, sympathetic overactivity, and hyperinsulinemia in hypertension and obesity, but the precise relation has not been clarified.The goal of the present longitudinal study was to clarify the interrelation of serum UA level, sympathetic activity, insulin, and leptin levels in subjects with weight gain-induced blood pressure (BP) elevation. We sequentially studied the accompaniments of spontaneous weight gain-induced BP elevation for 5 years, especially focusing on serum UA, sympathetic activity, and plasma levels of insulin and leptin.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…1,2,5,6 Furthermore, several large cohort studies have demonstrated close associations between obesity, especially abdominal obesity and the onset of chronic kidney disease (CKD) [7][8][9][10][11] and faster CKD progression. 10 Intentional weight loss (WL) reduced the risk of the onset and development of hypertension, 12,13 diabetes 14 and renal injury 15 in overweight or obese individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Many large studies [24][25][26] have shown marked clinical benefits of lifestyle intervention, and modest WL, on the resolution of obesity-relate diseases including CKD as well as long-term benefits on all-cause mortality. In obese subjects, obesity-related glomerular hyperfiltration, 27 elevated sympathetic nervous activity, 12,13,[28][29][30] insulin resistance and stimulation of the renin-angiotensin-aldosterone system (RAS) 30,31 are ameliorated after WL.…”
Section: Introductionmentioning
confidence: 99%